Nanostructured Pt and Pt-Sn catalysts supported on oxidized carbon nanotubes for ethanol and ethylene glycol electro-oxidation - Sieben, Juan Manuel (2011)
Pt and Pt-Sn catalysts supported on oxidized carbon nanotubes were prepared by multiple potentiostatic pulses and tested for ethanol and ethylene glycol electro-oxidation in sulfuric acid. The composed nanostructured materials were characterized via SEM, TEM, EDX and XRD analysis. Small metal nanoparticles (4-6 nm) forming 3-D nanostructured agglomerates (25-100 nm) distributed over the carbon substrate were formed. XRD results showed that the bimetallic electrocatalysts consisted of a Pt single-phase material, suggesting the formation of solid solutions over the entire composition range. The tin content in the alloys was between 10 and 40 at. %. Cyclic voltammetry and chronoamperometry measurements at room temperature showed that at potentials below 0.5 V, the bimetallic catalyst with 40 at. % Sn exhibited the highest activity for ethanol and ethylene glycol oxidation, whereas at potentials above 0.5 V, the alloy with 25 at. % Sn displayed better performance. This behavior can be explained by the synergistic effect between the facilitation of alcohol oxidation via oxygen-containing species adsorbed on Sn atoms, the alteration of the electronic structure of Pt atoms that weakens CO and intermediates adsorption, and the adequate Pt ensembles size. Besides, the increment of the lattice parameter and the presence of grain boundaries can enhance the adsorption of the alcohols and favor the splitting of the C-C bond. © 2010, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.